Analisis Konflik Vertikal Pertambangan Emas Tanpa Izin di Desa Kalirejo Kabupaten Kulon Progo - Dimas Asto Aji An' Amta (Universitas Lambung Mangkurat, 2023)
The period from 1995 to 2001 was the heyday of the people of Kalirejo Village as gold miners. After the victory, the gold yields decreased slowly, and made the village community, especially landowners, choose to rent their land to newcomers. The participation of newcomers then creates problems for the village: This study dismantles the dynamics of the conflict that occurred in Kalirejo Village and looks at the positive side of the conflict using Lewis Coser's concept. The author uses a qualitative method, namely descriptive analytic with a collective case study strategy to look at the conflicts that occurred in the period from 2009 to 2014 From these conflicts there are positive sides which are then used as learning by the village community as the basis for making regulations at the hamlet level. The roots of the conflict so far are fighting over productive economic resources and unclear policies from local governments regarding PETI activities.